Analisis Faktor-Faktor yang Mempengaruhi Tingkat Keberhasilan Usaha Penjualan Tanaman Hias di Denpasar - PRATIWI, KADEK ITA MEGA; ARTINI, NI WAYAN PUTU; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Analysis Determinant Factors Of Success Rate Of Sales Business of Ornamental Plant In Denpasar The success of a business is the goal of establishing a business. All businesses must know the factors that influence the level of success of their business. One of them is an ornamental plant sales business that has promising business opportunities. This study aims to identify the factors that influence the success rate of ornamental plant sales business in Denpasar and the constraints experienced by ornamental plant sellers during their business of selling ornamental plants. The sampling technique in this study was done by using purposive sampling technique. The analysis technique used is multiple linear regression analysis. The results showed that the influence of venture capital, education level, business duration, working hours and location had a positive and significant effect on the success rate of the business of selling ornamental plants. Barriers experienced by ornamental plant sellers are in the form of economic constraints such as capital difficulties, land leases. Technical barriers such as lack of understanding of the use of social media technology, and social barriers are competition from traders. Through this research, it is expected that the sellers of ornamental plants can allocate their capital well, the sellers are expected to be able to understand the market situation so that they get more buyers and must be able to keep up with the times by marketing their products through Instagram, Facebook and other social media.